Chondroitin sulfate-functionalized lipid nanoreservoirs: a novel cartilage-targeting approach for intra-articular delivery of cassic acid for osteoarthritis treatment - Heba M. K. Ebada; Maha M. A. Nasra; Rasha A. Nassra; Ossama Y. Abdallah (Drug Delivery, 2022)
Novel intra-articular nanoreservoirs were implemented employing different cartilage targeting approaches to improve cartilage bioavailability of a chondroprotective drug, cassic acid (CA), for effective amelioration of cartilage deterioration off-targeting CA gastrointestinal disorders. Herein, we compared active cartilage-targeting approach via chondroitin sulfate (CHS) functionalization versus passive targeting using positively charged nanoparticles to target negatively charged cartilage matrix. Firstly, CA integrated nanoreservoirs (CA-NRs) were fabricated based on ionic conjugation between CA and cationic hydrophobic surface modifier octadecylamine (ODA) and were further functionalized with CHS to develop CHS-CA-NRs. Confocal laser microscope was used to visualize the accumulation of nanoparticles into the cartilage tissue. Both targeting approaches promoted CA local cartilage availability and prolonged its residence time. Compared to passive targeted CA-NRs, active targeted CHS-CA-NRs showed higher fluorescence signals in proximity to and inside chondrocytes which lasted for up to 21 days. In MIA-osteoarthritic rats, CHS-CA-NRs showed superior antiosteoarthritic activity, exhibiting highest cartilage repair compared to CA-NRs. Additionally, CHS-CA-NRs significantly inhibited OA inflammatory cytokine, degradation enzyme and oxidative stress and improved cartilage matrix biosynthesis. Conclusively, CHS-CA-NRs improved OA repair showing a superior efficacy for articular cartilage targeting with CHS which could be a potential advance for OA therapy.